Characterization of Buckwheat 19-kD Allergen and Its Application for Diagnosing Clinical Reactivity - Choi, Soo-Young; Sohn, Jung-Ho; Lee, Yong-Won; Lee, Eun-Kyung; Hong, Chein-Soo; Park, Jung-Won (International archives of allergy and immunology, 2007)
Background: The 19-kD protein of buckwheat (BW) has been suggested to be a major allergen, but its characteristics and clinical significance are poorly defined. Methods: cDNA of the 19-kD BW allergen was cloned and expressed in Escherichia coli. Allergenicity and cross-allergenicity were confirmed by inhibition immunoblotting or by ELISA inhibition. The recombinant (r19-kD) protein was assessed for clinical utility in the diagnosis of BW reactivity in 18 BW-allergic and 19 BW-asymptomatic sensitized subjects using receiver operating characteristic analysis. Results: The 19-kD BW allergen, which is composed of 135 amino acids, has a weak homology to the vicilin-like allergens of cashew (Ana o 1), English walnut (Jug r 2) and 7 S globulin from Sesamum indicum. The r19-kD protein can inhibit sIgE binding to native 19-kD BW allergen. The maximum percentage inhibition of sIgE binding to crude BW extract was 56%. About 83.3% of the BW allergy patients had sIgE bound to r19-kD protein, compared to only 1 of the 19 BW-asymptomatic sensitized subjects. The areas under the receiver operating characteristic curves for the skin prick tests [0.925 (95% confidence interval: 0.839–1.012), p < 0.001] as well as r19-kD protein sIgE ELISAs [0.860 (95% confidence interval: 0.725–0.995), p <0.001] were higher than that of BW sIgE coated allergen particle test results [0.803 (95% confidence interval: 0.661–0.945), p = 0.002]. Conclusions: The 19-kD BW allergen may be the major allergen from BW. For the diagnosis of clinical reactivity to BW, the r19-kD protein sIgE ELISA test was more discriminative than the coated allergen particle sIgE measurement using whole BW extract.